Demostrar la siguiente desigualdad donde reales positivos $a$ , $b$ , $c$ satisface $ab+bc+ca=1$ . $$ \frac{a+b}{\sqrt{ab(1-ab)}} + \frac{b+c}{\sqrt{bc(1-bc)}} + \frac{c+a}{\sqrt{ca(1-ca)}} \le \frac{\sqrt{2}}{abc} $$ Lo tengo. $ \frac{a+b}{\sqrt{ab(1-ab)}}=\frac{a+b}{\sqrt{ab(bc+ca)}}=\frac{a+b}{\sqrt{abc(a+b)}}.$
Racionalizando, obtenemos $\frac{a+b}{\sqrt{abc(a+b)}}=\frac{(a+b){\sqrt{abc(a+b)}}}{abc(a+b)}=\frac{\sqrt{abc(a+b)}}{{abc}}$
Entonces basta con demostrar que $\sum_{cyc}\sqrt{abc(a+b)}\le \sqrt2.$
¿Alguna ayuda?